Carcinoma erysipeloides as a presenting feature of breast carcinoma: A case report and brief review of literature - Ali Al Ameer; Maryam Imran; Feroze Kaliyadan; Rajan Chopra (Wolters Kluwer Medknow Publications, 2015)
Carcinoma erysipeloides (CE) is an uncommon but distinctive form of cutaneous metastasis that usually manifests clinically as a fixed erythematous patch or plaque resembling cellulitis or erysipelas. The inflamed area may show a distinct raised edge at the periphery and also edema secondary to lymphatic obstruction. Histologically, dense carcinoma cells in the dermal vascular channels and dense perivascular lymphocytic infiltrate may be seen. CE may rarely be the first sign of "silent" tumor of breast. We report a case of a 52-year-old married lady who presented with a three months history of pruritic erythematous patches over the left side of the breast that was resistant to all topical treatments and was diagnosed as erysipeloid breast carcinoma.